ISOLATION AND CHARACTERIZATION OF PGPR ASSOCIATED WITH CAULIFLOWER ROOTS AND ITS EFFECT ON PLANT GROWTH - A. KUSHWAHA; S. B. BAILY; A. MAXTON; G. D. RAM (The Bioscan, 2013)
Four PGPR isolates of bacteria, designated as AK1, AK2, AK3 and AK4 were successfully isolated and characterized. To investigate the effects of PGPR isolates on the growth of cauliflower, a pot culture experiment was conducted. Isolates AK1, AK2, AK3 and AK4 showed the production of indole acetic acid (IAA), whereas the isolates AK2, AK3 and AK4 isolate were able to solubilize phosphorus. All the isolates resulted in a significant increase in plant height, root length and dry matter production of shoot and root of cauliflower plant compared to the control. PGPR were characterized based on its cultural, morphological and biochemical characters. Pot experiments showed that the PGPR treated seeds grew better than the untreated seeds. The present work suggests that the use of PGPR isolates AK1, AK2, AK3 and AK4 as inoculants biofertilizers might be beneficial for cauliflower cultivation as they enhanced growth of cauliflower by inducing IAA production and phosphorus solubilization.